Antidumping policy in the EU: A comment to the Green Paper on trade defence instruments - Brian Hindley (European Centre for International Political Economy (ECIPE), 2007)
The European Union is currently reviewing its policy for trade defence instruments; instruments purported to defend European producers from unfair trade practices such as dumping and subsidized exports as well as protect them from sudden surges of imports. In a Green Paper published late last year, the European Commission offers a justification for trade defence instruments but also signals an ambition to take account of changes in the global economy. It is a commendable ambition to provide a justification - an economic rationale - of the use of trade defence instruments, in particular antidumping, the most frequently used instrument. Antidumping practice is not transparent and often rests on convoluted investigations. It can easily degenerate into protectionism. An unambiguous rationale is therefore warranted to enable outside scrutiny of applied practices. But the European Commission fails to give a convincing justification of antidumping. Its overall defence of antidumping confuses the concepts of trade defence instruments and disregards basic economic analysis.
Keywords: 330; Antidumping; Handelshemmnisse; Transparenz; Protektionismus; EU-Staaten